Perancangan Prototipe Aplikasi e-Incident Berbasis Android di Rumah Sakit PKU Muhammadiyah Gamping - Dian Herawati; Nia Fararid Askar; Dinar Nugroho Pratomo (Jurnal Rekam Medis dan Informasi Kesehatan, 2022)
Recording and reporting of accidents and occupational diseases is a part of health information system that must be owned by the hospital. One of the efforts to achieve zero accidents is to take advantage of information technology such as android in increasing the effectiveness of recording and reporting OHS incident. The purpose of the study was to analyze the needs and create a prototype of an android based application. This research is qualitative with research and development design. The results show that it is necessary to add an incident reporting component related to hazardous and toxic substances. The application can answers the problems such as the delay in manual reporting and the documents are still fragmented. An e-incident application has a menu for reporting incidents, occupational diseases, and hazardous toxic substances. The menus have been made in accordance with OHS incident reporting standards in hospitals. The conclusion is that an android based e-incident application prototype has been made and can be accepted by users because it provides convenience and accuracy of data in OHS reporting in hospitals.